FATIGUE IN PATIENTS WITH SJÖGREN’S SYNDROME AND INTERVENTION OF TRADITIONAL HERBALMEDICINE - Li, Yizhe; Zhang, Jie (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Fatigue is the main complaint exiting in patients with primary Sjögren’s Syndrome (pSS) but rarely addressed. Patients described it as an uncontrollable symptom of lack of energy, which has negative impacts on health related quality of life. To date, many studies have demonstrated that cytokines, depression, sleep and endocrine disturbance interrelated with pSS-related fatigue. However, the pathogenesis remains unclear. With a long history, Traditional Chinese Medicine (TCM) as alternative therapy has become increasingly popular among patients with various kinds of disease, especially in pSS. Based on the unique principle of therapy, practitioners have achieved a satisfactory effect on relieving disease-related symptoms with Chinese Herbal Medicine (CHM). Materials and Methods: In this article, we succinctly reviewed the highly correlated factors to pSS-related fatigue from the standpoint of western medicine. Then, from TCM perspective, we illustrated that theoretic mechanisms lead to fatigue in patients with pSS. Results: According to the theory of TCM, we concluded that CHM as complementary and alternative medicines are attractive options to alleviate pSS-related fatigue. Conclusion: In clinic, physicians should remember to inquire whether their patients are worn out easily. Combination of Yin-tonifying and Qi-tonifying CHM may be the optimal options to pSS-related fatigue.